Microbiological Analysis Conducted on Raw Milk Collected During Official Sampling in Liguria (North-West Italy) over a Ten-Year Period (2014–2023) - Sara Antonia Chiarlone; Andrea Gori; Serena Ravetta; Andrea Armani; Lisa Guardone; Francesca Pedonese; Salvatore Bavetta; Caterina Fiannacca; Nicola Pussini; Cristiana Maurella; Elisabetta Razzuoli (Animals)
Milk has been consumed by humans for thousands of years for its nutritional properties. In recent years, raw milk demand has increased, valued for its authenticity and connection to local traditions. In Italy, the sale of raw milk is allowed exclusively through direct sale from the producing farm to the final consumer, either at the producing farm itself or through vending machines. However, the consumption of raw milk is not without risks. Among these, microbiological ones are relevant. These can lead to severe symptoms, particularly in vulnerable populations. For this reason, although consumers are advised to boil raw milk before consumption, producing farms in Italy are required to meet the microbiological criteria outlined in the Provision of 25 January 2007. In this retrospective study, the results of the analyses performed on 355 raw milk samples collected in Liguria between 2014 and 2023 for the detection of Campylobacter spp., Salmonella spp., Listeria monocytogenes, Staphylococcus aureus, and Escherichia coli O157 were analysed to better characterise the associated risk for consumers. The samples were collected during official controls by the local veterinary health services at vending machines of seven producing farms. Overall, six samples tested positive for C. jejuni, while only one sample tested positive for Salmonella enterica subsp. enterica, Serovar Veneziana. Listeria monocytogenes, S. aureus, and E. coli O157 were never responsible for non-compliances. Interestingly, three of the six samples positive for C. jejuni derived from the same producer. In farms where positive samples were detected, certain structural and/or operational non-compliances were identified. It can be concluded that, although the scenario in question does not present any cause for concern, it is nevertheless essential to implement a series of preventive measures in order to guarantee the safety of raw milk. These measures include the implementation of biosecurity practices, the maintenance of strict hygiene protocols during milking, and the adherence to the cold chain distribution protocol until the final stage of distribution.